2015
DOI: 10.3109/08830185.2015.1096937
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action of Probiotic Bacteria on Intestinal and Systemic Immunities and Antigen-Presenting Cells

Abstract: Immunomodulation has been shown to be one of the major functions of probiotic bacteria. This review is presented to provide detailed information on the immunomodulatory properties of probiotics in various animal models and clinical practices. Probiotics can regulate helper T (Th) responses and release of cytokines in a strain-specific manner. For example, Lactobacillus rhamnosus GG can induce beneficial Th1 immunomodulatory effect in infants with cow's milk allergy and relieve intestinal inflammation in atopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 69 publications
3
36
0
2
Order By: Relevance
“…Previous animal and in vitro studies suggest that immunomodulatory effects of probiotics are related to an increase of Tregs . However, similar to previous clinical studies on the effects of probiotics in children, we did not find that maternal probiotics affected the Tregs .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Previous animal and in vitro studies suggest that immunomodulatory effects of probiotics are related to an increase of Tregs . However, similar to previous clinical studies on the effects of probiotics in children, we did not find that maternal probiotics affected the Tregs .…”
Section: Discussionsupporting
confidence: 79%
“…Early intestinal microbiota is essential for normal maturation of the immune system and T cell balance, and unfavourable composition of the microbiota is associated with T cell inflammation in AD . Probiotic bacteria have the ability to modify the Th balance through their effects on dendritic cells, but there are conflicting results on the distinct effects of probiotics on T cell subsets in children. Some studies have reported a skewing towards a Th1 profile with increase in interferon gamma (IFNγ), while others have reported no effect on either the Th1/Th2 balance or Tregs .…”
Section: Introductionmentioning
confidence: 99%
“…Randomised controlled trials demonstrated that probiotics were effective in the modulation of symptom’s pattern of IBS patients [1924]. However, the majority of the studies have been performed in non-specific IBS rather than in PI-IBS D, so that the exact role of probiotics in the management of these patients remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Modulatory effects on DC have been postulated as a critical mechanism for probiotic-mediated immune modulation (Amar et al, 2015;Dongarrà et al, 2013;Fong, Kirjavainen, Wong, & El-Nezami, 2015;Fong, Shah, Kirjavainen, & El-Nezami, 2015;Martínez-Abad et al, 2016;Yang et al, 2015). However, direct evidence linking the effects of LAB on DC functionality and food allergy is scarce.…”
Section: Discussionmentioning
confidence: 99%